2017
DOI: 10.22159/ajpcr.2017.v10i10.18930
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Markers of Oxidative Dna Damage in Type 1 Diabetic Children: Relation to Microvascular Complications

Abstract: Objective: Type 1 diabetes mellitus (T1DM) is a widespread metabolic disease, which frequently carries with it a significant impact on human health. Oxidative damage and tissue inflammation have been claimed to be a typical pathogenic component for the progression of diabetic complications. We aim in this study to explore the relation of urinary 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodG) (as a marker of nucleic acid oxidation) to microvascular complications in T1DM.Methods: A case–control study, enrolling 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Diabetic overweight and obese children were significantly 3.8 folds more at risk to be bad glycemic control than diabetic children with normal BMI. This result comes in line with that of El-Wakeel et al's study [42]; this strong association was confirmed by many other studies [8], [18].…”
Section: Figure 2: Correlation Between Body Mass Index and Interleukisupporting
confidence: 92%
“…Diabetic overweight and obese children were significantly 3.8 folds more at risk to be bad glycemic control than diabetic children with normal BMI. This result comes in line with that of El-Wakeel et al's study [42]; this strong association was confirmed by many other studies [8], [18].…”
Section: Figure 2: Correlation Between Body Mass Index and Interleukisupporting
confidence: 92%
“…Type 1 diabetes mellitus (T1DM) is one of the most common pediatric chronic diseases, in which a progressive autoimmune T cell-mediated β cell destruction of pancreatic islets in genetically susceptible individuals (Wang et al 2017), resulting in loss of insulin secretion (Larsson et al 2016). Numerous studies have reported an increasing incidence of type 1 diabetes in children worldwide (Patterson et al 2015;El Wakeel et al 2017;Sabry et al 2018). It has major health consequences for individuals and societies.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with greater urine 8-oxodG levels had significantly faster development of diabetic kidney disease, according to clinical trial with a 5-year follow-up [56]. It has been shown that urinary 8-oxodG has a pathogenic role in the development of diabetic retinopathy in patients with both T1DM and T2DM [57]. According to Etiane et al, 8-oxodG has an AUC of 0.836, making it a diagnostic tool for assessing microvascular problems in diabetes patients [58].…”
Section: Biomarker Of Oxidative Stressmentioning
confidence: 99%